Analyzing conflict and its management within ICT4D partnerships: an institutional logics perspective. Issue 1 (2nd January 2018) - Ismail, Shahifol Arbi; Heeks, Richard; Nicholson, Brian; Aman, Aini
ABSTRACT: Promotion and presence of partnerships have been growing within information and communication technology for development (ICT4D). Yet – despite limited analytical literature on this topic – it is clear that the reality of ICT4D partnerships often undershoots the potential, with frequent reports of failure, particularly arising from conflict between partners. This paper addresses calls for more and better-conceptualized research into ICT4D partnerships, with a specific focus on understanding the roots and management of conflict in such partnerships. We use qualitative field data from a Malaysian IT "impact sourcing" public–private partnership case study, viewed through the lens of institutional logics and conflict management strategies. Analysis of three vignettes from the negotiation of the initiative shows one partner always used a competitive approach to conflict management. This led issues to remain unresolved and led the partnership arrangement to steadily loosen. The outcome was always domination of private logic over public logic. As a result, and lacking an overt advocate, welfare goals of the partnership were somewhat sidelined. Our paper contributes by showing (a) how institutional logics helps explain the outcome of ICT4D partnerships, and (b) how the conflict management strategies framework helps explain the practice of conflicting institutional logics in such partnerships.